Kearifan lokal perahu Sandeq sebagai bentuk warisan para leluhur suku Mandar - Saifullah Saifullah; Rahma Aulia; Muhammad Rafli Al Qadri (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
Sulawesi Island is a region rich in cultural diversity and traditions. One area with strong cultural distinctiveness is Majene Regency in West Sulawesi Province, inhabited by the Mandar people. The Mandar people are known as strong sailors and possess a maritime cultural heritage in the form of traditional boats, the Lopi Sandeq, which symbolize the resilience and pride of the Mandar people. This research used qualitative methods with observation and documentation techniques. The results show that the Sandeq is the fastest sailing ship in the world and a maritime icon of Mandar. The Passiluba Lopi tradition, or Sandeq boat race, is a form of preserving the cultural values, skills, and religious beliefs of the Mandar people that still survives today.